Analisis Pemanfaatan Internet di Pusat Pemerintahan Kabupaten Badung - Suarimbawa, I Made Rai; Linawati, Linawati; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro; Vol 17 No 2 (2018): (May - Agustus) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2018.v17i02.P04, 2018)
Abstract — Dishubkominfo as ICT implementing agency, currently serves internet connection of all SKPD in Badung Regency Government Center with bandwidth capacity of 200 Mbps and complaints about the stability and speed of internet access is still a lot going on, both from the internal use of SKPD or external from the community. This problem needs to be addressed by analyzing the characteristics of internet utilization traffic and user behavior in each SKPD so that bandwidth management policy will be right on target. This study aims to monitor and model characters from users using NetFlow and NFDUMP.   Based on the study results at Badung District Government Center, it was observed that TCP protocol has the highest level of network usage, followed by UDP protocol, and several other protocols. In terms of traffic sources, it is known that social media is the most frequently accessed site by the user. The results of this study can be used as a consideration in increasing the network bandwidth capacity and policies implemented in the Government Center of Badung Regency associated with internet access .